2015
DOI: 10.3402/ejpt.v6.27905
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-related dissociation and altered states of consciousness: a call for clinical, treatment, and neuroscience research

Abstract: The primary aim of this commentary is to describe trauma-related dissociation and altered states of consciousness in the context of a four-dimensional model that has recently been proposed (Frewen & Lanius, 2015). This model categorizes symptoms of trauma-related psychopathology into (1) those that occur within normal waking consciousness and (2) those that are dissociative and are associated with trauma-related altered states of consciousness (TRASC) along four dimensions: (1) time; (2) thought; (3) body; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 85 publications
(78 reference statements)
2
76
0
3
Order By: Relevance
“…The remaining recall period corresponded to a non-dissociative state, i.e. an ordinary recall episode without any of the above altered states of consciousness (Lanius, 2015). We hypothesised that higher HR would be associated with flashbacks and mixed periods of trauma recall since these states may involve greater emotional arousal.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining recall period corresponded to a non-dissociative state, i.e. an ordinary recall episode without any of the above altered states of consciousness (Lanius, 2015). We hypothesised that higher HR would be associated with flashbacks and mixed periods of trauma recall since these states may involve greater emotional arousal.…”
Section: The Current Studymentioning
confidence: 99%
“…Accordingly, it is important to investigate ways of detecting emotional arousal (e.g. fear and perceived threat) and different states of consciousness such as depersonalisation, derealisation, and flashbacks (Lanius, 2015) during voluntary recall of trauma among individuals with PTSD.…”
mentioning
confidence: 99%
“…For example, Westphal et al (2011) reported that individuals with a previous diagnosis of PTSD who did not currently meet criteria for the disorder experienced reduced quality of life when compared to trauma-exposed controls. Despite these findings, limited research has sought to identify symptom level factors predictive of functional impairment among individuals with PTSD – knowledge that is central to tailoring treatment to promote both symptomatic and functional recovery (Lanius, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Lanius (2015) further outlines how the model could guide treatment for trauma-affected patients, as TRASC of different dimensions of consciousness may require different treatments, something that future clinical studies could investigate. Studies on the impact of dissociation on treatment show inconsistent results, with some studies finding dissociation to predict poorer response (Bae, Kim, & Park, 2016; Kleindienst et al, 2016) while others fail to find such an effect (Minnen & Harned, 2012; Zoet, Wagenmans, van Minnen, & de Jongh, 2018).…”
Section: Discussionmentioning
confidence: 99%